A Liquid Metal Artificial Muscle. Issue 43 (12th September 2021) - Shu, Jian; Ge, Du‐An; Wang, Erlong; Ren, Hongtai; Cole, Tim; Tang, Shi‐Yang; Li, Xiangpeng; Zhou, Xiangbo; Li, Rongjie; Jin, Hu; Li, Weihua; Dickey, Michael D.; et al.
Abstract: Artificial muscles possess a vast potential in accelerating the development of robotics, exoskeletons, and prosthetics. Although a variety of emerging actuator technologies are reported, they suffer from several issues, such as high driving voltages, large hysteresis, and water intolerance. Here, a liquid metal artificial muscle (LMAM) is demonstrated, based on the electrochemically tunable interfacial tension of liquid metal to mimic the contraction and extension of muscles. The LMAM can work in different solutions with a wide range of pH (0–14), generating actuation strains of up to 87% at a maximum extension speed of 15 mm s −1 . More importantly, the LMAM only needs a very low driving voltage of 0.5 V. The actuating components of the LMAM are completely built from liquids, which avoids mechanical fatigue and provides actuator linkages without mechanical constraints to movement. The LMAM is used for developing several proof‐of‐concept applications, including controlled displays, cargo deliveries, and reconfigurable optical reflectors. The simplicity, versatility, and efficiency of the LMAM are further demonstrated by using it to actuate the caudal fin of an untethered bionic robotic fish. The presented LMAM has the potential to extend the performance space of soft actuators for applications from engineering fields to biomedical applications. Abstract : A liquid metal artificial muscle (LMAM) based on the electrochemically tunable interfacial tension of EGaIn liquid metal is demonstrated to mimic the contraction and extension of muscles. The actuating components of the LMAM are completely built from liquids, which avoids mechanical fatigue and provides actuator linkages without mechanical constraints to movement. Various proof‐of‐concept applications are demonstrated using the LMAM.